BEHAVIOR OF NAILED-SLAB SYSTEM ON SOFT CLAY DUE TO REPETITIVE LOADINGS BY CONDUCTING FULL SCALE TEST - Puri, Anas; Hardiyatmo, Hary Christady; Suhendro, Bambang; Rifa'i, Ahmad (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The Nailed-slab System is not a soil improvement method, but rather as an alternative method to improve the performance of rigid pavement on soft soils. The installed piles under the slab were functioned as slab stiffeners. This research is aimed to learn the behavior of Nailed-slab System under repetitive loadings and its consideration for practical application. The full scale Nailed-slab System was conducted on soft clay which consisted of 6.00 m x 3.54 m slab area with 0.15 m in slab thickness, 15 short micro piles (0.20 m in diameter, 1.50 m in length, and 1.20 m in pile spacing) as slab stiffeners which installed under slab. Piles and slab were connected monolithically, then in due with vertical concrete wall barrier on the two ends of slab. The system was loaded by vertical repetitive loadings. Results show that the installed piles under the slab which embedded into the soils were functioned as slab stiffeners and were able to response similarly in 3D. This system has higher resistance due to vibration. Thereby, the Nailed-slab system is promising for practical application.